AKTUALISASI ASURANSI SYARIAH DI ERA MODERN - Yovenska L.Man (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2017)
Abstract: Takaful is one of the most promising undertakings. People are expected to be involved in it, because of the principle of mutual help (tawa’un). Basically, Takaful and conventional insurance have advantages and disadvantages of each. Therefore, as a customer must understand and can consider well which insurance is most appropriate to use. Muslims should use sharia insurance or gradually abandon conventional insurance. The Takaful company obtains profit sharing from the management of funds collected on the basis of the tijarah (mudaraba) agreement. Takaful companies receive ujrah (fee) from the fund management of akar tabarru ‘(grant). There are several other tijarah contracts other than mudharabah that can be used in the practice of Takaful insurance, namely akad wakalah, wadi`ah and musyarakah.